Isolation and identification of amylolytic bacteria from garbage and garden soil (Bangladesh Journal of Botany, 2019)
An analysis for the abundance and diversity of amylolytic bacteria of two different soil types viz. garbage and garden soil was carried out. pH of the garbage and garden soil samples ranged between 7.73 and 9.84, 6.88 and 7.93, respectively. Average bacterial load on both NA and PYG agar media was found to be higher in garbage than garden soils. Bacterial load of garbage soil samples ranged from 2.08 × 108 to 3.79 ×108 cfu/g and 1.45 × 108 to 2.74 × 108 cfu/g on NA and PYG agar, respectively. On the other hand, bacterial load of the garden soil samples ranged from 3.3×106 to 9.7 ×106 cfu/g on NA and 2.9 × 106 to 9.35 × 106 cfu/g on PYG agar. A total of 200 bacterial isolates (100 from each soil type) were primarily selected for their amylolytic potential. Among them, the percentage of amylolytic bacteria was higher in garbage soil (46) than garden soil (38). Finally, a total of 8 (4 from each soil type) amylolytic potential isolates were selected for detailed study and identification. All 4 isolates from garbage soil and 3 from garden soil were found to be Gram positive and by conventional identification belonged to the genus Bacillus with six different species viz. Bacillus azotoformans (2), B. stearothermophilus (1), B. acidocaldarius (1), B. subtilis (2) and B. megaterium (1) and the only Gram negative isolate was identified as Acetobacter liquefaciens. The conventional identification was further confirmed by molecular technique and isolates were identified as Bacillus sp. T5-12, B. cereus MSW, Bacillus sp. FJAT-14266, B. toyonensis KK25A, B. cereus T10, Stenotrophomonas sp. ZJZG10, B. subtilis XF-1 and Pseudomonas sp. NCCP-1179. As significance of amylase enzyme in various industries and biotechnological processes are on the rise, it is important to find better and cheaper source for it. This piece of work focuses on finding out which can be a better source for amylolytic bacteria between two different soil types.